Challenges experienced by nursing students during the COVID‐19 pandemic. Issue 1 (4th August 2021) - Cengiz, Zeliha; Gurdap, Züleyha; Işik, Kevser
Abstract: Purpose: This study was conducted to assess the challenges faced by nursing students during the pandemic and to examine the factors affecting these challenges. Design and Methods: This qualitative study involved 344 nursing students at a university in eastern Turkey. Findings: Five main themes, each with its own subthemes, indicated the psychological difficulties experienced by students, insufficiencies and uncertainties regarding education, restrictions regarding social life, family conflicts, and the possibility to turn crises into opportunities. Practice Implications: The themes emphasizing the lives of nursing students showed that there was a need for important measures, such as psychosocial support, determination of best practices for online education, supporting students with telemental applications by university counseling centres, and organization of action courses.